Matti Kuusi’s Classification of Proverbs as a Proverbial Worldview - Lauhakangas, Outi (Tautosakos darbai, 2026)
Academician Matti Kuusi saw Finland as a convenient vantage point from which to make an international comparison of proverbs. His international type system of proverbs, which is online and free to use, is a comprehensive mapping of the human lifecycle, living conditions and social interaction. Kuusi’s typology can be regarded as a suggestion for a general pattern of worldviews maintained by proverb lore. The concept of proverbial worldview will be defined in this article. An analysis of Kuusi’s categorisation of proverbs comparing it with the main functions of proverb use in social interaction sheds light on the universal and national character of the proverb genre.